Phenology and diversity of adult stoneflies (Plecoptera) of a small coastal stream, California - Bottorff, Richard L. (Illiesia, 2007)
Collections of adult stoneflies over a full year at Irish Gulch Creek, Mendocino Co., California, revealed 23 species. Adults were present at all times of the year. Species number varied from an autumnal low of 2 to a springpeak of 13. Adults of most species were present for less than 3 months, but Malenka depressa adults were present year-round. Hesperoperla hoguei was the only strictly autumnal-emerging species. The report of Suwallia dubia fromIrish Gulch Creek represents a new California record. The stonefly faunas of Irish Gulch Creek (low coastal) and Sagehen Creek (high Sierra Nevada) werecompared. Both creeks had similar numbers of species, but the species composition differed greatly, reflecting dissimilar environments (elevation, water temperature, thermal accumulation, and discharge). Irish Gulch Creek haduniform warmer temperatures; Sagehen Creek had variable colder temperatures. Peak emergence at Irish Gulch Creek occurred 2 months earlier than at Sagehen Creek.
Keywords: entomologija; Plecoptera; insekti; vrbnice; California; Kalifornija; United States of America; ZDA